2018
DOI: 10.5812/jhealthscope.80335
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Fatigue and Job Burnout Dimensions in Hospital Nurses

Abstract: Background: Fatigue, as a destructive phenomenon, can have adverse effects on various aspects of workers' lives. Job burnout is one of the important consequences of fatigue among employees including nurses in different workplaces, especially healthcare centers. Objectives: The present study aimed to assess the relationship between fatigue and job burnout. Methods: This cross sectional study was conducted on 522 nurses, who were randomly selected from teaching hospitals of Shiraz University of Medical Sciences … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 25 publications
2
7
0
Order By: Relevance
“…These findings were in agreement with those of the study conducted by Asadi et al [ 40 ] and the Cochran study, which demonstrated moderate chronic fatigue among the participants [ 41 ]. The results were also consistent with those of a study performed using the Seman-Perlie Questionnaire [ 42 ], and research carried out by Azmoon et al using the Multidimensional Fatigue Inventory (MFI) [ 43 ]. In contrast, Choobineh et al [ 31 ] and Batak et al (using the Piper Fatigue Scale (PFS)) [ 44 ] reported high levels of fatigue.…”
Section: Discussionsupporting
confidence: 91%
“…These findings were in agreement with those of the study conducted by Asadi et al [ 40 ] and the Cochran study, which demonstrated moderate chronic fatigue among the participants [ 41 ]. The results were also consistent with those of a study performed using the Seman-Perlie Questionnaire [ 42 ], and research carried out by Azmoon et al using the Multidimensional Fatigue Inventory (MFI) [ 43 ]. In contrast, Choobineh et al [ 31 ] and Batak et al (using the Piper Fatigue Scale (PFS)) [ 44 ] reported high levels of fatigue.…”
Section: Discussionsupporting
confidence: 91%
“…Participants with fatigue were 2.5 times more likely to have psychological distress as compared with their counterparts. This is supported by a study from Iran [50] and Rhine-Main-Region, western Mid-Germany [51]. This might be for a reason that nurses with fatigue are commonly experienced with a devastating sense of drowsiness, lack of energy, and impaired cognitive and/or physical functioning, which may lead to a health problem, decrement of performance, increased risk of injury/accident, and low personal achievement, which possibly experience psychological distress [52][53][54].…”
Section: Discussionmentioning
confidence: 95%
“…Its manifestations on nurses can be mirrored in a combination of physical (eg, sleepiness) and psychological features (eg, compassion fatigue and emotional exhaustion . In addition, work‐related fatigue may lead to interpersonal consequences including decreased quality of communications with colleagues and patients . It also leads to physiological consequences including nurse injuries and adverse health outcomes like smoking, overweight and obesity, musculoskeletal problems, cardiovascular diseases, and diabetes mellitus .…”
Section: Introductionmentioning
confidence: 99%
“…, 15 In addition, work-related fatigue may lead to interpersonal consequences including decreased quality of communications with colleagues and patients. 16 It also leads to physiological consequences including nurse injuries and adverse health outcomes like smoking, overweight and obesity, musculoskeletal problems, cardiovascular diseases, and diabetes mellitus. 11,12,17 Of note, it is reported that 38% of nurses make medical errors related to fatigue.…”
Section: Introductionmentioning
confidence: 99%